2020
DOI: 10.3390/ijerph17155560
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Perception of Green Space for Health Promotion on Willingness to Use Parks and Actual Use among Young Urban Residents

Abstract: Promoting the use of green space is a fundamental way to improve physical and mental health and to enhance the quality of life of urban residents. In response to increasing demand for green space in cities, the impact of perception of green space for health promotion on willingness to use parks and actual use among young urban residents was investigated in this study. A total of 1135 young residents (ages 18–35) in three cities in China were surveyed by online questionnaire. A group of multiple regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 119 publications
3
36
0
Order By: Relevance
“…In addition, according to the results of observed people of different activity groups and their graphic spatial distribution (see Figure 4 and Appendix C ), the overall recreational spaces of four parks are more applicable for sightseeing and some activities that do not depend on facilities. Together with other studies [ 56 , 57 , 58 ], the results infer that places with sports courts/facilities for ball sports activities are generally scarce in Chinese parks [ 48 ], which results in fewer sports activity groups in parks.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In addition, according to the results of observed people of different activity groups and their graphic spatial distribution (see Figure 4 and Appendix C ), the overall recreational spaces of four parks are more applicable for sightseeing and some activities that do not depend on facilities. Together with other studies [ 56 , 57 , 58 ], the results infer that places with sports courts/facilities for ball sports activities are generally scarce in Chinese parks [ 48 ], which results in fewer sports activity groups in parks.…”
Section: Discussionsupporting
confidence: 72%
“…The purpose of urban parks, especially large ones, is to serve different kinds of activities and high service quality exists when recreation opportunities meet the needs of various visitors [ 46 ]. However, it was reported that Chinese young people were less likely to use parks [ 47 ] and this was related to a lack of attractiveness for young adults of urban parks in China [ 48 ]. As a result, the diversity of activity types that visitors engaged in should also be an important index to assess a park’s service quality.…”
Section: Introductionmentioning
confidence: 99%
“…A well-defined and visible entrance gives comfort to users and allows them to enter the POS. Wide, single-level walkways within POS improve usability and provide physical comfort not only to joggers but also to senior citizens who prefer walking [45][46][47]. Furthermore, the climate responsive design of POS also improves physical comfort [48,49].…”
Section: Public Open Space Index (Posi)mentioning
confidence: 99%
“…The construction of ecological civilization has been incorporated into China's national master plan, elevating ecological construction to the national strategic level. As people's living standards have improved, the importance of green space for mental health, especially for stress relief, has attracted the attention of the Chinese public ( 2 , 3 ). As an aspect of urban construction, greening is responsible for a city's ecological functioning and has been shown to exert significant positive effects on Chinese residents' mental health ( 4 ) and well-being ( 1 ).…”
Section: Introductionmentioning
confidence: 99%